TEORI KEAGENAN DALAM PERSPEKTIF ISLAM - Achmad Uzaimi (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2017)
The agency theory is a reference that has been widely used in accounting studies. But there is a fundamental difference between the assumptions used and the reality of Islamic values. Islam directs the agreement between the owner and the agent to a trusting relationship driven by a fraternal spirit based on the Qur'an and the Hadith. Principals and agents carry out their responsibilities by prioritizing tawakkal rather than their intellect, carrying on noble character in the execution of agreed contracts.